THE EFFECTS OF TEAM ASSISTED INDIVIDUAL COOPERATIVE LEARNING SUPPLEMENTED WITH EXERCISES BOOK BASE ON NUMBER SENSE AND LEARNING LOG OF PRATHOMSUKSA 4 STUDENTS - Keawbunsri , Jitwirune; Saenpluem, Busawan (Journal of MCU Nakhondhat, 2023)
The purposes of this research article were :1) to study mathematical achievement of Students 2) to compare mathematical achievement of Students on fraction between before and after learn 3) to study mathematical writing ability. The research was a one group pretest-postest design. The population were Prathomsuksa 4 students in 2/2021 academic year in normal curriculum classroom 8 classroom, 360 students. The sample group were Prathomsuksa 4 students in 2/ 2021 academic year 1 classrom, 46 students with mixed abilities which was obtained from cluster random sampling. The research Instrument included lesson plans, Exercises Book based on Number Sense, learning logs,a achievement test, a mathematical writing ability test. The trial was run alternately between even and odd numbers. Under the 2019 coronavirus situation lasted 4 hours a week, a total of hours, a total of 11 weeks. for all Mean, standard deviation, percentage were used for data analysis. A t-test for one sample and t-test for dependent samples were used for testing hypotheses. The findings of this research were as follows: 1) Students who study with team assisted individual cooperative learning supplemented with exercises book based on number sense and learning log that have mathematical achievement test score after learning were 27.61 or 76.70 percent. The students’ posttest score was not less than 75 percent. 2) Students who study with team assisted individual cooperative learning supplemented with exercises book based on number sense and learning log that have mathematical achievement test score were 13.22 or 36.70 percent and 27.61 or 76.70 percent respectively. The students’ mathematical achievement test score after the experiment was higher than that of the pretest. 3) Students who study with team assisted individual cooperative learning supplemented with exercises book based on number sense and learning log that have mathematical writing ability test score after learning were 27.04 or 75.12 percent.The students’ posttest score was not less than 75 percent.